Enhancing the creep resistance in a RE-free cast Mg-Al-Ca alloy through microalloying of Ti - Zhuang Cui; Yang Liu; Ying Zeng; Manping Liu; Xiaochun Liu; Shiwei Xu; Xuefei Chen; Qudong Wang (Journal of Magnesium and Alloys)
High temperature performance of magnesium alloys can be tailored by either grain size or precipitates in the grain interior. In this study, exceptional creep resistance was successfully acquired in a RE-free cast Mg-Al-Ca-Ti (AC51Ti) alloy. Microalloying of Ti (0.01 wt.%) has been found to be beneficial to the improvement of the tensile creep resistance in a RE-free cast Mg-5Al-0.35Mn-(1Ca) (AC51) alloy, showing a low state creep rate (SCR) of 2.70 × 10−9 s−1 at 200 °C/50 MPa, which is even better than that of many reported RE-containing Mg alloys. The presence of trace Ti contributes to the substantial refinement and more uniform distribution of Al2Ca precipitates in the matrix. At the same time, the microalloying of Ti improves the solubility of Al and Ca in the matrix. It is reasonable to believe that the microalloying of Ti induced re-organization of Al2Ca precipitates, dissolved a larger amount of Al and Ca atoms into magnesium lattice, and increased the possibility of interaction between GB/dislocations and precipitates, which strongly correlates with the high temperature properties. The creep strengthening mechanisms primarily attributed to both second phase strengthening and solid solution strengthening were separately proposed based on the experimental investigations.